The effects of hospital and dialysis unit characteristics on hospitalizations for access-related complications among children on maintenance dialysis: a European, multicenter, observational, cross-sectional study - Atikel, Yeşim Özdemir; Schmitt, Claus Peter; Lévai, Eszter; Adalat, Shazia; Shroff, Rukshana; Goodman, Nadine; Dursun, İsmail; Pınarbaşı, Ayşe Seda; Yazıcıoğlu, Burcu; Paglialonga, Fabio; Vondrak, Karel; Guzzo, Isabella; et al. (Pediatric nephrology, 2023)
BACKGROUND: Previous studies investigating hospitalizations in dialysis patients have focused primarily on patient-centered factors. We analyzed the impact of hospital and dialysis unit characteristics on pediatric dialysis patients' hospitalizations for access-related complications (ARCs). METHODS: This cross-sectional study involved 102 hemodialysis (HD) and 163 peritoneal dialysis (PD) patients. Data between July 2017 and July 2018 were analyzed. RESULTS: Children's hospitals (CHs) had more pediatric nephrologists and longer PD experience (years) than general hospitals (GHs) (p = 0.026 and p = 0.023, respectively). A total of 53% of automated PD (APD) and 6% of continuous ambulatory PD (CAPD) patients were in CHs (p < 0.001). Ninety-three percent of APD and 69% of CAPD patients were treated in pediatric-specific PD units (p = 0.001). CHs had a higher prevalence in providing hemodiafiltration (HDF) than GHs (83% vs. 30%). Ninety-seven percent of HDF vs. 66% for conventional HD (cHD) patients, and 94% of patients with arteriovenous fistula (AVF) vs. 70% of those with central venous catheters (CVC), were dialyzed in pediatric-specific HD units (p = 0.001 and p = 0.016, respectively). Eighty patients (51 PD and 29 HD) had 135 (84 PD, 51 HD) hospitalizations. CAPD was an independent risk factor for hospitalizations for infectious ARCs (I-ARCs) (p = 0.009), and a health center's PD experience negatively correlated with CAPD patient hospitalizations for I-ARCs (p = 0.041). cHD and dialyzing in combined HD units significantly increased hospitalization risk for non-infectious (NI-)ARCs (p = 0.044 and p = 0.017, respectively). CONCLUSIONS: CHs and pediatric-specific dialysis units have higher prevalence of APD and HDF use. Hospitalizations for I-ARCs in CAPD are lower in centers with longer PD experience, and pediatric HD units are associated with fewer hospitalizations due to NI-ARCs. A higher resolution version of the Graphical abstract is available as Supplementary information.
Keywords: nemocnice; Child; Renal Dialysis; Cross-Sectional Studies; Kidney Failure, Chronic; Peritoneal Dialysis; hospitalizace; Humans; chronické selhání ledvin; dialýza ledvin; Hospitals; peritoneální dialýza; lidé; Hospitalization; průřezové studie; dítě